Echocardiography Quiz - Kyriakakis, C.G.; Brauns, R.; Barnard, B.J.; Doubell, A.F.; Herbst, P.G. (SA Heart Journal, 2017)
A 65-year-old female patient presented to our medical emergency department with dyspnoea at rest due to acute pulmonary oedema without chest pain. She had been treated for an acute coronary syndrome with transient STelevation in the infero-lateral leads 12 days prior to this admission. Angiography on her initial admission revealed a chronic total occlusion of her left circumfl ex artery and a reperfused, non-obstructive lesion of the right coronary artery that was treated medically. Examination revealed a pulse rate of 115 bpm and BP 70/45mmHg and no murmurs were audible over the precordium. She required invasive ventilatory support for her pulmonary oedema.